Noncompact Perturbation of Sweeping Process with Delay in Banach Spaces - F. Aladsani; A. G. Ibrahim (International Journal of Mathematics and Mathematical Sciences)
We have proven an existence theorem concerning the existence of solutions for a functional evolution inclusion governed by sweeping process with closed convex sets depending on time and state and with a noncompact nonconvex perturbation in Banach spaces. This work extends some recent existence theorems concerning sweeping processes from Hilbert spaces setting to Banach spaces setting. Moreover, it improves some recent existence results for sweeping processes in Banach spaces.